Vitellibacter nionensis sp nov., isolated from a shallow water hydrothermal vent - Rajasabapathy, Raju; Mohandass, Chellandi; Yoon, Jung-Hoon; Dastager, Syed Gulam; Liu, Qing; Thi-Nhan Khieu; Chu Ky Son; Li, Wen-Jun; Colaco, Ana (International Journal of Systematic and Evolutionary Microbiology, 2015)
A novel, Gram-stain-negative, non-motile, rod-shaped yellow bacterium, designated VBW088(T) was isolated from a shallow water hydrothermal vent in Espalamaca in the Azores. Phylogenetic analysis based on 16S rRNA gene sequences showed that strain VBW088(T) clustered with three type strains of species of the genus Vitellibacter and exhibited a sequence similarity of 97.3% with Vitellibacter soesokkakensis RSSK-12(T). However, strain VBW088(T) and V. soesokkakensis RSSK-12(T) exhibited low DNA-DNA relatedness (12.7 +/- 3.5 %). Strain VBW088(T) was positive for catalase and oxidase. Growth occurred at 10-37 degrees C, with the optimum at 80 degrees C, and at pH 6.0-8.0 (optimum pH 6.0) and in up to 5% (w/v) NaCl with optimum growth at 1-2% (w/v) NaCl. The major fatty acids (>10%) were iso-C-15:0 (33.5%) and iso-C-17:0 3-OH (32.0%). The polar lipids detected in strain VBW088(T) consisted of phosphatidylethanolamine, one unidentified aminolipid and three unidentified phospholipids. The DNA G+C content of strain VBW088(T) was 36.7 mol%. On the basis of phylogenetic inference, DNA-DNA relatedness, chemotaxonomic analysis and physiological data, the isolate represents a novel species of the genus Vitellibacter, for which the name Vitellibacter nionensis sp. nov. is proposed, with the type strain as VBW088(T). (=KCTC 32420(T)=MCC 2354(T)).